HUBUNGAN MOTIVASI DENGAN KEPATUHAN PELAKSANAAN DIET PADA PENDERITA DIABETES MELITUS - Manurung, Tumpal; Manalu, Rina Marlina; Manurung, Yolanda (Universitas Prima Indonesia, 2020)
Planning diet is a major component of the successful management of Diabetes Mellitus. The success of meal planning depends on the behavior of people with Diabetes Mellitus in choosing food include the amount of energy, the type of food, and the meal schedule. Compliance is the individual's behavior to carry out the instructions suggested by the doctor. The purpose of this study was to analyze the relationship of motivation with compliance with diabetes mellitus diet in patients with diabetes mellitus at Porsea Regional Hospital. The research design used was a cross-sectional approach. The population of Diabetes Mellitus patient at Porsea Regional Hospital was 21 respondents. The measuring instrument uses a questionnaire of motivation and compliance with diabetes mellitus diet. Data were analyzed by the Pearson Product Moment correlation test. The result of Pearson Product Moment test analysis obtained significant value 0.000 which means there is a significant relationship between the relationships of motivation with compliance diabetes mellitus diet in people with diabetes mellitus at Porsea Regional Hospital. The motivation is important because it is related to dietary changes diabetes mellitus patients are based on the patient's desire to heal and reduce the risk of complications caused by diabetes mellitus so they are motivated to follow the recommended diet program. It is expected that the nursing and doctor always motivate people with diabetes mellitus to compliance the Diabetes Mellitus diet to reduce the complications of diseases caused by Diabetes Mellitus.